2022
DOI: 10.3390/ma15196939
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Ultrasonic Welding Parameters for Multilayer Lap Joints of PEEK and Carbon Fibers by Neural Network Simulation

Abstract: The aim of this study is to substantiate the use machine learning methods to optimize a combination of ultrasonic welding (USW) parameters for manufacturing of multilayer lap joints consisting of two outer PEEK layers, a middle prepreg of unidirectional carbon fibers (CFs), and two energy directors (EDs) between them. As a result, a mathematical problem associated with determining the optimal combination of technological parameters was formulated for the formation of USW joints possessing improved functional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…However, failure is to be guaranteed to occur adhesively along the fusion zone (between the adherends) in the studied cases. Since the neat PEI plates were welded, the USW joints could be fractured through the base material [26]. Respectively, the applied strength criterion was the  f parameter.…”
Section: Resultsmentioning
confidence: 99%
“…However, failure is to be guaranteed to occur adhesively along the fusion zone (between the adherends) in the studied cases. Since the neat PEI plates were welded, the USW joints could be fractured through the base material [26]. Respectively, the applied strength criterion was the  f parameter.…”
Section: Resultsmentioning
confidence: 99%
“…The main cracks initiated at their junctions with the PEI adherends (which were stress raisers) and propagated along the interlayer interface. This phenomenon caused additional bending of the PEI plates [37], so the high adhesion level slowed down the process, according to the authors. The final fracture stage was of a cohesive type.…”
Section: Tensile Testsmentioning
confidence: 95%
“…The DIC method [39,40] was applied to experimentally confirm the macroscopic bending of the USW lap joints during the tensile tests (previously investigated by computer simulation based on the finite-element method [37]), as well as to assess strain distributions in both the PEI plates and the fusion zone. The TecaPEI lap joint fabricated using mode #5 was tested under static tension at a cross-head speed of 1 mm/min.…”
Section: Deformation Behavior Characterization By the Dic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A brief overview of the application of machine learning methods using small experimental data samples. As the authors have shown previously [ 42 ], the issue of finding an optimal combination of USC parameters cannot be considered as an optimization problem, since the conditions for ensuring the optimality of the functional characteristics of such lap joints are represented by a system of inequalities. This formulation is determined not only by the inconsistency of the requirements (formulation of criteria) for their individual properties, but also by the specifics of the problem.…”
Section: Introductionmentioning
confidence: 99%